Evidence comes by replication, but needs differentiation: the reproducibility issue in science and its relevance for criminology - Lösel, Friedrich (Journal of experimental criminology, 2018)
Recent publications in Nature, Science, and other journals raised concerns about the reproducibility of empirical findings in psychology and other scientific disciplines. This article summarizes some of these arguments and results that led to discussions about a “replication crisis” in research. In criminology, there is not yet a similar discussion, although the need for more replications has been emphasized in the past. The present article addresses this topic with special consideration of program evaluations in early developmental crime prevention and offender treatment. In both fields, there has been substantial progress in research and practice. Most systematic reviews showed mean positive effects; however, nearly all of them demonstrated very heterogeneous findings that could not be attributed to the content of programs. This does not allow simple recommendations of “what works” for policy-making and practice. In addition, there is a serious lack of long-term follow-ups and independent evaluations. The article shows remarkable similarity of the findings and problems in both fields of intervention. Problems of reproducibility prove to be highly relevant for criminology, although there is no need for using the term “crisis”. The article proposes various strategies that can enhance the reproducibility of findings, i.e., more systematic investigation of those differentiated conditions under which interventions are most effective. An integrative model of relevant characteristics is briefly presented. It refers to factors of the programs, contexts, participants, and evaluation methods. Confirmatory meta-analyses can play an important role on the path toward more differentiated and replicated knowledge